Patterns of the initiation of disease-modifying antirheumatic drugs in incident rheumatoid arthritis: a German perspective based on nationwide ambulatory drug prescription data - Steffen, A.; Holstiege, J.; Klimke, K.; Akmatov, M. K.; Batzing, J. (Rheumatol Int, 2018)
This study aimed at providing a current and nearly complete picture of the patterns of the initiation of disease-modifying antirheumatic drugs (DMARDs) in patients with newly diagnosed RA. Based on ambulatory drug prescription data and physician billing claims data covering 87% of the German population, we assembled a cohort of incident RA patients aged 15-79 years (n = 54,896) and assessed the prescription frequency of total DMARDs, conventional synthetic (csDMARDs) and biologic DMARDs (bDMARDs) within the first year of disease. Using multiple logistic regression, we estimated the chance of early DMARD receipt based on age, sex, serotype and specialty of prescribing physician while controlling for region of residence. In total, 44% of incident RA patients received a DMARD prescription within the first year of disease. In multiple regression, younger patients (< 35 years) had 1.7-fold higher chances of receiving a csDMARD than patients aged >/= 65 years [odds ratio (OR): 1.65 with 95% confidence interval (CI) 1.51-1.80] and almost tenfold higher chances to receive a bDMARD [OR (95% CI) 9.5 (8.0-11.3)]. Seropositivity and a visit to a rheumatologist were positively associated with DMARD initiation [OR (95% CI) 2.8 (2.6-2.9) and 5.9 (5.6-6.2) for csDMARDs, respectively]. Based on data covering 87% of the German population, the present study revealed that less than half of incident RA patients receive DMARDs within the first year of disease and that marked differences exist according to age. The study highlights the importance of involving a rheumatologist early in the management of RA.